PEMBUANGAN BAYI DALAM PERSPEKTIF PENELANTARAN ANAK - Airlangga Justitia (Universitas Bengkulu, 2018)
The act of disposing of a newly born child is obviously a criminal offense, since this act does not necessarily reflect the humanism side of the human person. an act which the rule of law is proclaimed as a prohibited act is called a criminal act or it may be referred to as a crime. According to its nature and nature, these criminal acts are unlawful acts. These acts can also harm society, in the sense of contradicting or impeding the implementation of the social order of society that is considered good and fair. There are 3 (three) legal instruments that contain criminal sanctions against the perpetrators of the crime of infant / child disposal namely the Criminal Code, Law No. 23 of 2004 on the Elimination of Domestic Violence, and Law No. 35 of 2014 on Child Protection. However, newly born child abusers are still not eliminated, and one of the factors is the lack of conviction of criminal prosecution.